(untitled) (Conferencea, 2022)
Today, economic sanctions are one of the most common foreign policy instruments. Sanctions have taken a firm place in foreign policy tools as an alternative or addition to the use of force, as well as to reinforce negotiating positions. They are actively used as a means of forcing individual states to comply with the political requirements of the countries that initiated the sanctions. The use of sanctions by the UN Security Council is on the rise. At the same time, mechanisms are being improved to circumvent sanctions and mitigate their impact on the national economies and stability of the “target states”. Often, the application of sanctions becomes a matter of normative and ethical disagreement between the targets of sanctions (usually developing countries) and the initiators of sanctions (usually developed countries). The initiators see sanctions as one of the legitimate ways to enforce compliance with international obligations or certain norms. The countries subjected to sanctions perceive them as a threat to their national security, a "bad trick" that is abused by the countries that initiate the sanctions, which have economic and technological superiority. At best, these countries recognize the legitimacy of the sanctions imposed by the UN Security Council, but not the unilateral measures of developed countries